2015
DOI: 10.1108/ijqrm-05-2013-0075
|View full text |Cite
|
Sign up to set email alerts
|

Service quality, customer satisfaction and loyalty in automobile repair services sector

Abstract: Purpose – The purpose of this study is to explore the dimensional structure of the SERVQUAL scale within non-western service setting as well as the impact of service quality dimensions on customer satisfaction and loyalty. Design/methodology/approach – A quantitative approach was employed, using 32-item, seven-point Likert-scaled questionnaire administered to 384 participants with 55.99 per cent usable response rate. Data were analysed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
164
2
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(192 citation statements)
references
References 42 publications
10
164
2
16
Order By: Relevance
“…Izogo and Ogba (2015), Dedeoğlu and Demirer (2015) and Zamil, Areiqat and Tailakh (2012) all found the same results. In contrast, Qin, Prybutok and Zhao (2010) found that only three attributes, tangibles, reliability and responsiveness, were particularly salient dimensions in fast food restaurants in China.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Izogo and Ogba (2015), Dedeoğlu and Demirer (2015) and Zamil, Areiqat and Tailakh (2012) all found the same results. In contrast, Qin, Prybutok and Zhao (2010) found that only three attributes, tangibles, reliability and responsiveness, were particularly salient dimensions in fast food restaurants in China.…”
Section: Discussionsupporting
confidence: 70%
“…That is, service quality is an outcome of the difference between service expectations and customer perceptions of actual service performance (Naik, Gantasala, & Prabhakar, 2010;Yeşilada & Direktör, 2010). Izogo and Ogba (2015) argued that service quality leads to enhanced customer satisfaction and loyalty as a result of several factors. They added that SERVQUAL is one of the best measures of service quality.…”
Section: Service Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Sendo assim, apenas quando o prestador de serviços entende o processo de percepção e avaliação dos clientes, é que se torna possível influenciá-los para seguir na direção desejada. Além disso, a qualidade do serviço é tida como um determinante importante da satisfação do cliente, o que, por sua vez, influencia a fidelidade dos clientes (Izogo & Ogba, 2015).…”
Section: Características E Qualidade Dos Serviçosunclassified
“…Compared to physical products, service features are invisible, and the production and sale occurs simultaneously. As service occurs, customers also play a role in co-production (Izogo & Ogba, 2015), so it is not easy to measure the performance of service. Parasuraman et al (1985) proposed the concept of the service quality model, and established consumer perceptions of service quality systems.…”
Section: Golf Simulation Systemmentioning
confidence: 99%